Active DNA demethylation by Gadd45 and DNA repair - Niehrs, Christof; Schäfer, Andrea (Trends in cell biology, 2012)
How DNA methylation patterns are established, maintained and remodeled is incompletely understood, however, it has become clear that DNA methylation is reversible and dynamic as a result of enzymatic DNA demethylation. Several different mechanisms that may account for demethylation have recently been put forward and all seem to involve DNA repair. Here, we review DNA demethylation mediated by multifunctional growth arrest and DNA damage 45 (Gadd45) protein family members which mediate DNA demethylation during cell differentiation and stress response. Gadd45 recruits nucleotide and/or base excision repair factors to gene-specific loci and acts as an adapter between repair factors and chromatin, thereby creating a nexus between epigenetics and DNA repair.